Economic background crop rotation as a way to prevent the degradation of agricultural landscapes - Shevchenko, O.; Openko, І.; Tsviakh, О. (Land Management, Cadastre and Land Monitoring, 2017)
This article explores that to successfully combat land degradation on lands occupied in agriculture, it is necessary to conduct complex soil conservation measures constitute a single interconnected system and protect soil from degradation.Found that rotation – a reasonable compromise between the main requirements of production, organization of territory and environment, placing crops in view of a favorable combination; compliance with acceptable saturation parameters optimally varying cultures, and thus the possible timing of a return to their previous cultivation while taking into account the duration of the accepted rotation.Determined that the implementation and observance of crop rotation and better ensure the replenishment of nutrients of the soil, improving and maintaining its favorable physical properties, prevent the emergence of weeds, pests and pathogens cultivated crops and preventing the depletion of soil degradation processes and development.Found that scientifically based crop rotation is the basis for the use of all complex farming practices, differentiated cultivation, rational use of fertilizers and caring for plants. Rotation is correct – it agroecosystem, which created the best conditions for growth and development of various crops, thus providing a growing high and stable yields, obtaining high quality products.Soil and climatic conditions, specialty farms, crops structure and their biological characteristics defined as the type of crop rotation and crop rotation order. Each rotation should be selected such status, which would provide the greatest yield per unit area of rational use of all land. Therefore, proper placement crops in crop rotation must necessarily take into account the requirements of crops to their predecessor, thus it must evaluate not only the direct action of the first culture, but also take into account the impact of the latter on the following crops rotation.On unproductive and degraded lands is recommended rotation of soil saturation with large crops of grasses and crops of solid cover, which makes it possible to avoid or minimize the growing row crops.Introduce a rotation of soil combined with contour reclamation of the territory, which includes, band allocation of agricultural crops, construction of various water-regulating structures meadow to the degree of degradation of soil and the steepness of the slope. This limits the fields are projected across the slope or parallel horizontally, and to combat deflation - across the direction of prevailing winds.The study crop rotation over time as a way of preventing the degradation of agricultural landscapes allowed to establish scientifically grounded crop rotation not only performs reclamation feature - provides protection from degradation of the soil and creates a favorable ecological environment in agricultural landscapes, but also can have significant economic efficiency. By comparison the actual amount of sales of crop considering the cost of its production in the administrative districts of Kyiv region (2703,4 million UAH) with a forecast value of crop production while maintaining a crop pattern in the rotation with a corresponding set of crops (3075,8 million UAH) proved that the economic effect of the introduction of scientifically grounded crop rotations in the region will be about 372,4 million USD, and additional income from 1 hectare of crop area – 322,8 USD.It is proved that, in addition to rotation for a successful fight against land degradation on lands occupied in agriculture also need to implement complex soil conservation measures to protect soil from degradation. To determine the economically justified soil conservation measures were examined the economic impact and effectiveness of each in current market conditions.Keywords: crop rotation, crop rotation, degradation of agricultural landscapes, extra income.